Risiko Finansial, Risiko Produk, Hedonisme, Risiko Privasi, dan Niat Belanja Online - Ii Lidyaningsih; Gede Sri Darma (Universitas Pendidikan Nasional, 2022)
The decline in the income of business actors in the midst of the covid pandemic is a difficult test, but statistics show an increase in online transactions in Indonesia. This study aims to analyze andexamine the factors that influence millennial behavior in online shopping, including a hedonistic lifestyle, financial risk, product risk, and privacy risk. The location of the research was carried out in Denpasar City with the consideration that it is a metropolitan city and has a high economic turnover in the province of Bali. The sample in this study was millennials as many as 126 respondents who were divided based on quota sampling in four sub-districts in the city of Denpasar. The data collection technique used an open questionnaire with an interval scale of 1-10. The data analysis technique uses the Structural Equation Modeling (SEM) through the Part lease square (PLS) approach with the SmartPLS 3.2 program. The results of the study found that the hedonism variable had a positive and significant effect ton online shopping intentions, while the financial risk and product risk variables had a significant negative effect on online shopping intentions and the privacy variable did not have a negative and significant effect on online shopping intentions. The majority of millennials believe and believe that online stores that have strong security and a good image will not abuse their privacy.